2019
DOI: 10.1039/c8ra10184a
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of amyloid fibrils on interaction with MoS2-based nanomaterials

Abstract: The present work computationally establishes that the structure and energetics of fibril-like biomacromolecules can be modulated by confining them on the MoS2 based nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Besides, MoS 2 can quench ·NO, as observed in ESR spin trapping experiments [ 80 ]. As well as their anti-redox activity, Mo-based NMs can inhibit Aβ aggregation, which has been confirmed by molecular dynamics simulations [ 76 , 81 ]. The results of the simulations showed that an MoS 2 nanotube could destabilize amyloid fibrils when they interacted.…”
Section: Nms Mimic Enzyme Activity To Scavenge Ronsmentioning
confidence: 77%
See 1 more Smart Citation
“…Besides, MoS 2 can quench ·NO, as observed in ESR spin trapping experiments [ 80 ]. As well as their anti-redox activity, Mo-based NMs can inhibit Aβ aggregation, which has been confirmed by molecular dynamics simulations [ 76 , 81 ]. The results of the simulations showed that an MoS 2 nanotube could destabilize amyloid fibrils when they interacted.…”
Section: Nms Mimic Enzyme Activity To Scavenge Ronsmentioning
confidence: 77%
“…The results of the simulations showed that an MoS 2 nanotube could destabilize amyloid fibrils when they interacted. Moreover, the surface of an MoS 2 nanotube can inhibit the growth of smaller protofibrils into mature fibrils and also break already-formed fibrils [ 81 ].…”
Section: Nms Mimic Enzyme Activity To Scavenge Ronsmentioning
confidence: 99%
“…In the same work, it has been proved that β-Si 3 N 4 nanosheets exhibit a semiconducting behavior with a band gap of about 2 eV. Taking into account the findings that semiconducting MoS 2 [24] or graphene [25] monolayers indeed destabilize amyloid beta fibrils [26], we therefore hypothesized that 2D Si 3 N 4 may exhibit the same effect based on the structural and electronic similarities. As a result, the present work was devoted to evaluating the biocompatibility of β-Si 3 N 4 monolayers as a first step in testing our hypothesis in case they are released in vivo.…”
Section: Introductionmentioning
confidence: 88%
“…The basal plane of TMD NSs can adsorb or conjugate various aromatics (e.g., pyridine and purine) and other compounds. Mudedla et al investigated the interaction between Aβ fibrils and MoS 2 -based materials and found that MoS 2 nanotubes could inhibit the aggregation of smaller protofibrils to matured fibrils and bust the preformed fibrils [144]. Wang The 2D TMDs analogous to graphene exhibit excellent properties, such as high colloidal stability in aqueous media and a high mass extinction coefficient at 800 nm [147].…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 99%